Sua nota tem valor? – Uma avaliação da nova sistemática do Programa de Educação Fiscal do Governo do Estado - Rego, Ana Virginia Gurgel (2023)
In the quest to balance cash inflows and outflows, the State has, among its possibilities for increasing its own resources, to increase the assessment of taxes due - a less burdensome option for the taxpayer than increasing the tax burden. This is one of the objectives of Tax Education – to make citizens aware that the cost of public services and goods comes mainly from the payment of taxes by society, and that social control and collaboration with the community are fundamental as a way of combating tax evasion and increasing collection, providing a wider range of public goods and services. The purpose of this study is to analyze whether the new methodology of Fiscal Education programs in Ceará, the most recent in a history of campaigns that began in the 1950s, the Sua Nota Tem Valor Program - SNTV, had an impact on ICMS collection, encouraging the consumer to request the tax document (invoice or coupon) at the time of purchase. To this end, it is used the difference-in-differences method, an inference technique that compares the behavior of the variable studied in two groups, at two moments: this study will analyze the ICMS collection in the retail segment in Ceará (which sells directly to end consumers, is therefore affected by the program's actions) with the State's non-retailer, between 2019 and 2021, in two periods – before SNTV and after its implementation. It is verified the relevance of the program by noting a positive variation in ICMS collection from the retail segment in 173 of the 184 municipalities in Ceará, with an average increase of 4.38%. Among the possible factors that contributed to this result, it is highlighted the number of registered participants and the number of supported institutions, which act as partners in the initiative.